The Priority of European Law over National Law of EU Member States and the Direct Application of European Law - Mădălina COCOŞATU (Acta Universitatis Danubius: Administratio, 2014)
Objectives: Since the early nineteenth century juridical thought was concerned to determine the relationship between international law and national law and at the end of the twentieth century began discussions on the relationship between EU law and national law. This study aims to analyze European law enforcement in the EU Member States. The essay also examines interdisciplinary the correlation between the principle of direct applicability of European law with the principle of the precedence of European law over national law of Member States. Prior work: I’ve tried to find and debate hermeneutical decisions of European Court of and doctrinal opinions in this domain very important for those who practice European law and international public law. Results: In European Union and Member States, the enforcement of principles of law is viewed with great interest, being considered sources of law. Value: We think this article represents an important step in the disclosure of the problem raised by appliance of European reglementation on national level.